Rafflesia tuanku-halimii (Rafflesiaceae), A New Species from Peninsular Malaysia - Jumaat, Haji Adam; Mohd Afiq, Aizat Juhari; Rahmah, Mohamed; Nor Azilah, Abdul Wahab; Syamsurina, Arshad; Mohd Paiz, Kamaruzaman; Mohd Firdaus, Mohd Raih; Wan, Kiew Lian (Universiti Kebangsaan Malaysia, 2016)
Rafflesia tuanku-halimii, a new species from Peninsular Malaysia, is herewith described and illustrated. It is related to R. azlanii and R. sharifah-hapsahiae by coalesced warts on it lobes. Rafflesia tuanku-halimii is different from them in having window covered by almost united rings and these rings almost wholly covering the window